2012
DOI: 10.1523/jneurosci.4676-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Reward Action in the Initiation of Smooth Pursuit Eye Movements

Abstract: Reward has a powerful influence on motor behavior. To probe how and where reward systems alter motor behavior, we studied smooth pursuit eye movements in monkeys trained to associate the color of a visual cue with the size of the reward to be issued at the end of the target motion. When the tracking task presented two different colored targets that moved orthogonally, monkeys biased the initiation of pursuit towards the direction of motion of the target that led to larger reward. The bias was larger than expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 41 publications
6
41
1
Order By: Relevance
“…Although reward did not affect the learning speed of simian smooth pursuit eye movements, it apparently did influence the expression of the learned pursuit eye movements (Joshua and Lisberger, 2012). Also, learning to use a robotic arm can be influenced by reward (Nikooyan and Ahmed, 2015) or punishment (Galea et al, 2015) in healthy human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Although reward did not affect the learning speed of simian smooth pursuit eye movements, it apparently did influence the expression of the learned pursuit eye movements (Joshua and Lisberger, 2012). Also, learning to use a robotic arm can be influenced by reward (Nikooyan and Ahmed, 2015) or punishment (Galea et al, 2015) in healthy human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…We modified a smooth pursuit eye movement leaning paradigm to test whether motor commands are needed for learning to occur. When monkeys (and humans) are trained to track a moving target that repeatedly undergoes the same change in direction at a predictable time, a learned smooth pursuit eye movement is elicited prior to change in target direction (Joshua and Lisberger 2012;Medina et al 2005). These behavioral changes occur quickly and asymptotically after a few as 50 trials (Hall et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on value-modulations of smooth pursuit showed that value information can bias the initial pursuit direction, when the rewarded direction is cued in advance (Joshua & Lisberger, 2012), or when spatially-defined targets were used (Ferrera, 2000). In our paradigm, the rewarded direction was not predictable which allowed us to directly compare the time course of salience and value effects.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, reward decreases smooth pursuit latency and increases acceleration slightly. These effects seem to be small in magnitude, compared to the effects on target selection (Joshua & Lisberger, 2012). Similar to pursuit, reward also leads to a decrease in saccade latency (Milstein & Dorris, 2007;Rothkirch et al, 2013;Takikawa et al, 2002) and an increase in saccade peak velocity (Chen et al, 2013;Takikawa et al, 2002;Xu-Wilson, Zee, & Shadmehr, 2009).…”
Section: Effects Of Reward With Single Targetsmentioning
confidence: 90%
See 1 more Smart Citation